"You Might Want to Call Your Father": An Autoethnographic Account of Masculinity, Relationships, and My Father. Issue 1 (2nd January 2016) - Strasser, Daniel S.
ABSTRACT: Autoethnographic scholarship interrogating father–son relationships and masculinity adds to our understanding of father–son relationships through the critique of dominant models of fathering that may harm intimacy. This autoethnography explores one turning point that occurred between the author and his father when they experienced the death of a mutual friend. This event became the catalyst in the relationship, which the author illustrates through narrative vignettes to show the struggles that exist, and highlights a view on father–son relationships and masculinities that challenges masculine norms in order to (re)create a valued relationship. The goal of this narrative is to offer an opportunity for others to reflect on identity, relationships, and masculinities in their own experiences and relationships.